'My first thoughts were Why?' Using Saul's (2001) six qualities to get to the pearl grit of reflection. Issue 2 (4th March 2022) - Eaton, Colette
ABSTRACT: Reflection and reflective practice continue to be crucial elements of teaching, learning and development in health and care professions and can be used to identify elements of self, including values and experience, which impact the care we deliver. Whilst students grasp that reflection is a task they need to carry out, they rarely consider the philosophical underpinning of what reflection is for and, may not realise that reflective thinking is a step beyond simply writing about an experience. Using Saul's notion of the Six Qualities which constitute human genius, I developed questions to guide reflection with these six qualities as themes then, working with two groups of undergraduate health and care students, delivered guided reflection workshops using found objects. Here I present some of the reflections recorded by the students during those workshops to show that, given time and a clear philosophical standpoint, students can be guided to consider the subjectivity of care and connection with others.